New species of Neosilba McAlpine (Diptera: Lonchaeidae) and new records from Colombia - Galeano-Olaya, Pedro E; Canal, Nelson A (Papéis Avulsos de Zoologia, 2012)
The Neotropical genus of lance flies Neosilba McAlpine could be found associated with fruits, flowers or buds of plants. There are few basic or applied studies of these insects, including data on taxonomy and/or economic importance. We described ten new species from Colombia: N. plana sp. nov., N. tolimensis sp. nov., N. amphora sp. nov., N. convexa sp. nov., N. concava sp. nov., N. orbata sp. nov., N. spiculata sp. nov., N. angusta sp. nov., N. distospinosa sp. nov. and N. piracea sp. nov. We presented a key for the all 40 valid species of the genus, included in five groups and two subgroups: major, parva, peltae, pendula and glaberrima groups. Glaberrima includes the two subgroups glaberrima and certa, and pendula includes the pendula and nigrocaerulea subgroups. Neosilba parva and N. bifida are reported for first time in Colombia.